Implikasi Penetapan Margin Keuntungan pada Pembiayaan Murabahah (Suatu Studi dari Perspektif Islam pada Baitul Qiradh Amanah) - Azharsyah Ibrahim; Fitria (Universitas Islam Negeri Ar-Raniry, 2012)
Murabahah is a particular kind of sale that compliant with shariah. In this scheme, the seller expressly mentions the cost he/she incurred on the commodities for sale and sells it to another person by adding some profit thereon which is known to the buyer. It is one of the most popular modes used by Islamic banks. With its fixed margin, it offers the seller a more predictable income stream. This study aims to analyze the implications of the determination of the profit margin for the murabahah financing at an Islamic microfinance called Baitul Qiradh Amanah. Primary data was collected mainly through interviews and observation. The observation was conducted for about two months. During the observation process, co-researcher was directly involved as a trainee at the Baitul Qiradh. Interviews were conducted to clarify some unclear information that was obtained through observation. To strengthen the primary data, the secondary data is also utilized through books, magazines, and other studies. The secondary data is then compared with the findings from the field which is then analyzed using content analysis. The results showed that the profit margins in the initial of profit determination unilaterally bring both positive and negative implications for the clients and the Baitul Qiradh itself. The positive implication is (1) the Baitul Qiradh is able to predict its profit and (2) the clients are prevented from the risk of inflation or economic crisis. While the negative implications are (1) eliminating bargaining power of clients and (2) affect to customer satisfaction that lead to the decrease of number of customers of the Baitul Qiradh. ABSTRAK - Pembiayaan murabahah adalah jual beli barang pada harga pokok dengan tambahan keuntungan yang disepakati. Dalam skema ini, margin keuntungan biasanya ditetapkan di awal sebelum transaksi terjadi. Penelitian ini bertujuan untuk menganalisis implikasi penetapan margin keuntungan pembiayaan pada sebuah lembaga keuangan mikro syariah, yaitu Baitul Qiradh Amanah. baik terhadap nasabah ataupun terhadap Baitul Qiradh itu sendiri. Data primer dikumpulkan dengan wawancara dan observasi. Observasi dilakukan selama lebih kurang dua bulan di mana salah seorang peneliti terlibat langsung sebagai trainee di Baitul Qiradh yang menjadi objek penelitian. Wawancara dilakukan untuk memperjelaskan hal-hal yang tidak bisa didapat melalui observasi. Di samping itu, untuk memperkuat data primer, peneliti juga mengumpulkan data sekunder melalui buku-buku, majalah, serta penelitian-penelitian lainnya. Data sekunder ini kemudian dibandingkan dengan temuan lapangan untuk kemudian dianalisis dengan cara content analysis. Hasil penelitian menunjukkan bahwa penetapan margin keuntungan di awal secara sepihak memunculkan implikasi positif maupun negatif baik terhadap nasabah atau Baitul Qiradh sendiri. Implikasi positifnya adalah jelasnya jumlah keuntungan yang didapat Baitul Qiradh dan menghindarkan nasabah dari risiko inflasi atau krisis ekonomi. Sedangkan implikasi negatif adalah menghilangkan daya tawar nasabah. Hal ini berimplikasi pada berkurangnya kepuasan nasabah untuk berurusan dengan Baitul Qiradh.